Mindring: Bridging Islamic Economic Principles and Business Practices in Indonesia’s Furniture Credit Industry - Lailyah, Nurzahroh; Karatri, Rhealin Hening; Pattipeilhy, Shary Charlotte Henriette (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
This study examines strategies for utilizing halal tourism as a driver of sustainable economic development in Central Java, Indonesia, a pilot province for this niche market. With a focus on Muslim travelers seeking culturally and religiously appropriate experiences, the research integrates primary data from stakeholder interviews and secondary data from local tourism records. The findings highlight that while Central Java’s halal tourism sector shows considerable potential, it remains in its early stages, with significant opportunities for growth. Key strategies identified include categorizing tourist destinations into historical, nature, and cultural segments to better tailor marketing and improve visitor experiences. Additionally, creating regional tourist routes is suggested to enhance accessibility and navigation for tourists. The study emphasizes the importance of aligning halal tourism efforts with sustainable economic growth, particularly in the context of the G20 agenda. By linking halal tourism with broader economic strategies, the research provides actionable insights for policymakers and industry stakeholders to strengthen local business capacities and boost the economic resilience of the region. This approach positions halal tourism not only as a cultural offering but also as a pivotal component of Central Java’s long-term economic development strategy.